The Economical Structure of the North-Eastern States of India from the British Colonial Period, A Brief Study - Mahanta, Madhurjya (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper represents an overview of the economic structure of the north-eastern states of India from the British colonial period, a brief study.
Keywords: Agriculture; assam; arunachal pradesh; british; development; economy; manipur; meghalaya; nagaland; northeast india; production; income Tripura